The Prevalence of Depressive and Insomnia Symptoms, and Their Association With Quality of Life Among Older Adults in Rural Areas in China - Yang, Juan-Juan; Cai, Hong; Xia, Lei; Nie, Weicheng; Zhang, Yulong; Wang, Song; Shi, Yudong; Ng, Chee H.; Liu, Huanzhong; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
ABSTRACT Background: There are few studies on the epidemiology of depression, insomnia, and their association with quality of life (QOL) in older adults living in rural China. This study examined the prevalence of depression and insomnia, and their association with QOL in community-dwelling older adults in a rural area in Anhui province, China. Methods: This was a cross-sectional study conducted between July and October, 2019 using random sampling method. Depression, insomnia, and QOL were assessed with standardized instruments. Results: A total of 871 older adults were included. The prevalence of overall depression, insomnia, and comorbid depression and insomnia was 34.0% (95% CI: 30.9-37.1%), 45.7% (95%CI: 42.4-49.0%) and 20.3% (95% CI: 17.7-23.0%), respectively. Older adults with depression, insomnia, and comorbid depression and insomnia had lower scores in QOL compared to those without. Depression was positively associated with living with families (OR=1.82, 95%CI: 1.31-2.54) and negatively associated with current drinking (OR=0.49, 95%CI: 0.33-0.72). Insomnia was negatively associated with fair and good financial status (fair: OR=0.53, 95%CI=0.38-0.75; good: OR=0.30, 95%CI=0.14-0.64) and current drinking (OR=0.64, 95%CI=0.45-0.93), and positively associated with more frequent major medical conditions (OR=1.32, 95%CI=1.16-1.51). Comorbid depression and insomnia were positively associated with living with families (OR=2.02, 95%CI=1.36-3.00), and negatively associated with fair and good financial status (fair: OR=0.61, 95%CI=0.41-0.89; good: OR=0.34, 95%CI=0.12-0.95) and current drinking (OR=0.57, 95%CI=0.35-0.92). Conclusion: Depression and insomnia were common in older adults living in rural areas in China. Considering the negative health outcomes caused by depression and insomnia, regular screening and effective treatments should be developed for this population.